What if you had animal eyes!? - Markle, Sandra; McWilliam, Howard, 1977- (2017)
"What if you woke up one morning and your eyes weren't yours? What If You Had Animal Eyes?--the next imaginative book in the What If You Had series--explores what would happen if you looked in the mirror and saw an pair of animal eyes instead of your own! From the chameleon's eyes that can point in different directions, to the colossal squid's eyes that shine in the dark, discover what it would be like if you had these special eyes--and find out why your eyes are just the right ones for you!"--
Ages 4-8.
K to grade 3.
Keywords: Eye -- Juvenile literature; Animals -- Juvenile literature; JUVENILE NONFICTION / Animals / General; JUVENILE NONFICTION / Science & Nature / Anatomy & Physiology; JUVENILE NONFICTION / Animals / Nocturnal